A price analysis of vegetables on the East London municipal market - Fraser, Gavin Cecil Gilbert (Rhodes University, Faculty of Commerce, Department of Economics, 1983)
[Introduction] Much of the information available on the prices of vegetables marketed through the fresh produce markets is of limited use to producers. This information contains the actual prices for individual years. This can obviously be taken as a guide to future prices but it does not necessarily mean that those prices are a true reflection of the general pattern. In this study an attempt will be made, firstly, to establish whether a general pattern exists in the prices of selected vegetables on the East London municipal market. This will be attempted by studying the prices obtained over the 1964-1979 period. Information of this nature can be used as a basis for the planning of future crops. Secondly, to determine the months which obtain the "best" prices for the selected vegetables taking into account the quantities supplied to the market.
Keywords: Agricultural prices -- South Africa